Research progress on insulin resistance in polycystic ovary syndrome - Qi, Yang-Bin; Yi, Peng; Fu, Xiang-Hong (Reproductive and developmental medicine, 2025)
Polycystic ovary syndrome (PCOS) is a common gynecological disease that affects women of reproductive age and is characterized by hyperandrogenism, ovulatory dysfunction, and polycystic changes in the ovaries. In recent years, along with irregular menstruation and infertility, metabolic abnormalities associated with PCOS have garnered increasing attention. Insulin resistance is the most prevalent metabolic abnormality in patients with PCOS and is closely related to disease progression and severity. Insulin-sensitizing drugs improve obesity- and hyperinsulinemia-related symptoms in patients with PCOS. Although the exact etiology of PCOS remains incompletely understood, genomic and metabolomic studies have identified various metabolic changes in the serum and follicular fluid of patients with PCOS and in animal models. These findings shed light on the pathogenesis of PCOS and help identify new preventive and therapeutic approaches. This review explores the role of insulin resistance in the pathophysiology of PCOS, focusing on its effects on ovulation and hyperandrogenism. It also summarizes recent therapeutic advancements, evaluates their efficacy, and discusses strategies for the long-term management of insulin resistance in PCOS.